Albumin: a novel biomarker for predicting intraoperative hypothermia in HSCR - Xiaohui Huang; Mobai Ren; Junrong Pan; Ene Huang; Yanhong Li; Donghao Guo; Junjie Wang (Annals of Medicine, 2025)
Background Intraoperative hypothermia is a significant life-threatening emergency during surgery in patients with Hirschsprung’s disease (HSCR). The aim of this study is to explore the risk factors and predictors of intraoperative hypothermia in HSCR patients.Methods This cohort comprised 85 patients with HSCR who underwent surgery at Quanzhou Children’s Hospital and the patients were divided into the intraoperative non-hypothermia group and the intraoperative hypothermia group. The study compared the characteristics of two groups and used univariate and multiple logistic regression analyses to assess the potential risk factors for intraoperative hypothermia. Models were adjusted for covariates, and interaction terms were evaluated for albumin (ALB) and intraoperative hypothermia. Subgroup analysis included stratification by sex and age. ROC analysis was applied to determine the optimal threshold for ALB.Results In this retrospective study, 71 patients had intraoperative non-hypothermia and 14 patients had intraoperative hypothermia (83.5% versus 16.5%). Comparing the clinical characteristics between two groups, baseline core temperature, ALB and alkaline phosphatase (p < .001, p = .001 and p = .036, respectively) showed significant differences. Univariate logistic regression showed that baseline core temperature (OR = 0.001, 95%CI = 0.000–0.024, p < .001), ALB (OR = 0.820, 95%CI = 0.679–0.972, p = .028) and gamma-glutamyl transferase (OR = 1.017, 95%CI = 1.001–1.035, p = .043) had significant associations with intraoperative hypothermia. Multiple logistic regression showed that both ALB (OR = 0.782, 95%CI = 0.611–0.965, p = .031) and baseline core temperature (OR = 0.001, 95%CI = 0.000–0.019, p < .001) were negatively associated with intraoperative hypothermia. The relationship between ALB and intraoperative hypothermia remained significant after adjusting for covariates. ROC analysis identified 41.45 g/L as the optimal threshold of ALB for predicting intraoperative hypothermia, with a sensitivity of 85.71% and a specificity of 64.79%.Conclusion ALB is an independent risk factor for intraoperative hypothermia in HSCR patients. Further investments are required to explore its mechanisms.